Parian Polyandreia : the late geometric funerary legacy of cremated soldiers' bones on socio-political affairs and military organizational preparedness in ancient Greece - Agelarakis, Anagnostis P., 1956- (Archaeopress Publishing Ltd, 2017)
This text centres on the anthropological study of two late 8th century BC monumental graves, designated as T144 and T105, at the ancient necropolis of Paroikia at Paros. The study investigates inter-island features of the human record, observable as ingrained traces in the skeletal record. These have particular significance as they may relate to Parian endeavours in the northern Aegean to colonise Thasos. Through the 'Paros Polyandreia Anthropological Project,' it was possible to gain insights into aspects of the human environment and experience in the Parian context. A considerable population sample of cremated male individuals was available, shedding light on trends that would have involved Thasos; and discerning further facets of the human condition during the Late Geometric to the Early Archaic periods in the ancient Hellenic world.